A new species of Pediobius (Hymenoptera: Eulophidae) from Epilachna (Coleoptera: Coccinellidae) in Costa Rica - Hansson, Christer; Nishida, Kenji (Revista de Biología Tropical, 2002)
A new and morphologically very distinct species of Pediobius from Costa Rica is described. The new species (P. nishidai) is unique among New World species of Pediobius in having the propodeum elongated and extended backwards (i.e. with an elongated nucha). The entire type series (15 females, two males) was reared from a single prepupa of Epilachna mexicana and it has been concluded that the new Pediobius species is a gregarious endoparasitoid that pupates inside its host. The possible use of this new species as a biological control agent against “the Mexican bean beetle” (E. varivestis) should be tested.